The Puzzle of Buddhist Non-Attachment: A Challenge for Laypersons - Joyitri Sarkar (Philosophies, 2025)
This article explores the challenges associated with practicing Buddhist non-attachment as a layperson and whether its application in everyday life represents a puzzle. In Buddhism, practicing non-attachment implies becoming free of desires, as prescribed by Mahāyāna Buddhist philosophy in pursuit of liberation. This raises a critical challenge to form and maintain friendships in this increasingly competitive and demanding environment. To thrive, one must pursue beneficial goals to ensure a meaningful existence. A layperson, therefore, cannot entirely detach from their goals and aspirations without potentially abandoning the Buddhist path to enlightenment. Thus, non-attachment presents a dilemma for laypersons, creating a challenge in reconciling Buddhist philosophy with the realities of worldly existence.